'This Is the View When I Walk into My House': Accounting Phenomenologically for the Efficacy of Spatial Methods with Youth. (August 2017) - Kennelly, Jacqueline
This article argues for the utility of phenomenology in accounting for the manner in which spatial methods yield insights into the everyday lived experiences of young people that are not as easily accessible through more traditional qualitative methods such as interviewing. Spatial methods, defined as methods that focus on the everyday spatial experiences of young people and methods that ask youth to position themselves in space, have been used by the author in a variety of research projects, and also incorporate certain visual methods. Phenomenological concepts such as the spatial perspective, the web of relations and opaque subjectivity are helpful in understanding not only that these methods work well but why they are so effective. The article also addresses Pierre Bourdieu's critique of phenomenology, responding to his concern that phenomenology might be susceptible to ignoring or overlooking the social and political contexts that shape experiences.